2016
DOI: 10.1002/smi.2725
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress following crime victimization: An exploratory study from an agency perspective

Abstract: Deficits in recognition of suffering play a significant role in the etiology of psychological distress in crime victims. However, given the preliminary status of the literature, it seems necessary to take other factors into account as well. Starting from an agency perspective, this study explored three such factors: negative self-attributions, peritraumatic distress, and early posttraumatic emotions. More specifically, this study explored whether the association between recognition deficits and posttraumatic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Furthermore, Posick and Policastro (2013), in a study using the 2009-2010 British Crime Survey, showed that victims of violent crimes report higher distress than those who were victims of nonviolent crimes, although those with prior victimizations report no difference in distress level compared to those without a prior victimization experience. Further illustrating the relevance of violent victimization, Kunst and Koster (2017), using a sample of crime victims in the Netherlands, found that victims of crime vary in their reports of post-traumatic stress disorder symptomology, with some evidence that violent victims report more PTSD symptoms.…”
Section: Distress From Victimizationmentioning
confidence: 99%
“…Furthermore, Posick and Policastro (2013), in a study using the 2009-2010 British Crime Survey, showed that victims of violent crimes report higher distress than those who were victims of nonviolent crimes, although those with prior victimizations report no difference in distress level compared to those without a prior victimization experience. Further illustrating the relevance of violent victimization, Kunst and Koster (2017), using a sample of crime victims in the Netherlands, found that victims of crime vary in their reports of post-traumatic stress disorder symptomology, with some evidence that violent victims report more PTSD symptoms.…”
Section: Distress From Victimizationmentioning
confidence: 99%
“…Most crime victims return to their pre-crime level of emotional wellbeing during this period of time and therefore will not benefit from speaking during the court hearing (cf. Kunst & Koster, 2017). The small proportion of crime victims that does not return to its pre-crime level of emotional wellbeing will, on the other hand, only benefit from clinical interventions.…”
Section: An Examplementioning
confidence: 99%
“…Beyond physical injury and property loss, the experience of being a victim of a criminal act has both short-and longterm negative effects on mental health [1][2][3][4][5][6][7][8][9][10][11][12]. Although the symptoms of posttraumatic stress disorder (PTSD) are the most severe psychological sequelae of violent offenses [3,10,[12][13][14][15][16], several researchers have identified a broad spectrum of other psychological symptoms among victims of violent and nonviolent crime [2, 4, 6-10, 17, 18]. As Tan and Haining [8] showed, 86% of crime victims questioned in Sheffield (UK) reported at least one psychological symptom as a consequence of a crime experience: stress (59.7%), sleeping difficulties (39.3%), lack of confidence (37.2%), depression (30.1%) and panic attacks (24.5%).…”
Section: Introductionmentioning
confidence: 99%